2015
DOI: 10.3892/ol.2015.3407
|View full text |Cite
|
Sign up to set email alerts
|

C-X-C motif receptor 7 in gastrointestinal cancer

Abstract: Abstract. Chemokine receptors are key mediators of normal physiology and numerous pathological conditions, including inflammation and cancer. This receptor family is an emerging target for anticancer drug development. C-X-C motif receptor 7 (CXCR7) is an atypical chemokine receptor that was first cloned from a canine cDNA library as an orphan receptor and was initially named receptor dog cDNA 1 (RDC1). Shortly after demonstrating that RDC1 binds with its ligand, stromal cell-derived factor-1α and interferon-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 65 publications
(120 reference statements)
0
5
0
Order By: Relevance
“…CXCR7 is usually upregulated in GC tissues with a positivity rate of 63–84.62% by IHC, which correlates with deep invasion, LN metastasis, advanced stages, and bad outcome of patients . Also, CXCR7 is highly expressed in the majority of tumor‐associated vessels and related with tumor neovascularization via regulating the secretion of proangiogenic factors such as interleukin‐8 and VEGF . CXCR7 overexpression may affect disease progression by stimulating proliferation, invasion, migration, adhesion, and angiogenesis of GC through β ‐arrestin‐dependent downstream signalings, including Akt, ERK1/2, p38 MAPK, JAK2/STAT3, and stress‐activated protein kinase (SAPK) pathways .…”
Section: Cross‐talks Of Cxcl12/cxcr4 Axis With Other Chemokines and Cmentioning
confidence: 99%
See 2 more Smart Citations
“…CXCR7 is usually upregulated in GC tissues with a positivity rate of 63–84.62% by IHC, which correlates with deep invasion, LN metastasis, advanced stages, and bad outcome of patients . Also, CXCR7 is highly expressed in the majority of tumor‐associated vessels and related with tumor neovascularization via regulating the secretion of proangiogenic factors such as interleukin‐8 and VEGF . CXCR7 overexpression may affect disease progression by stimulating proliferation, invasion, migration, adhesion, and angiogenesis of GC through β ‐arrestin‐dependent downstream signalings, including Akt, ERK1/2, p38 MAPK, JAK2/STAT3, and stress‐activated protein kinase (SAPK) pathways .…”
Section: Cross‐talks Of Cxcl12/cxcr4 Axis With Other Chemokines and Cmentioning
confidence: 99%
“…It is demonstrated that inhibition of CXCR7 pathway leads to an antitumor activity in various solid malignancies originated from colon, liver, pancreas, and head and neck . CCX754 as one of CXCR7 antagonists significantly suppresses the growth of lung cancer in both immunodeficient and immunocompetent mouse models, which are engrafted by human A549 and mouse LL/2 Lewis lung carcinoma cell lines, respectively .…”
Section: Cross‐talks Of Cxcl12/cxcr4 Axis With Other Chemokines and Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study demonstrated that the IL-8-regulated CXCR7 stimulated EGFR Signaling to promote prostate cancer growth (Singh, 2011). In a study conducted by Yun et al ., it is reported that CXCR7 expression was increased in most of the tumor cells compared with the normal cells and is involved in cell proliferation, migration, survival, invasion and angiogenesis during the initiation and progression of many cancer types including prostate cancer (Yun, 2015). It was also shown in (Lin, 2014) that elevated expression of CXCR7 contributes to HCC growth and invasiveness via activation of MAPK and angiogenesis signaling pathways and they also conclude that targeting CXCR7 may prevent metastasis and provide a potential therapeutic strategy for hepatocellular carcinoma (HCC).…”
Section: Literature Search Of the Top Hub Targetsmentioning
confidence: 99%
“…Chemokines are a group of small chemotactic cytokines that interact with seven-transmembrane G-protein-coupled receptors, and this interaction is involved in organ development, host immune responses and other physiological processes that direct cells to specific sites in the body (12,13). Approximately 50 human genes encode chemokine ligands, and >20 chemokine receptor (CCR) genes have been identified since the term 'chemokine' was originally introduced in 1992 as an abbreviated form of chemotactic cytokine (1,14).…”
Section: Introductionmentioning
confidence: 99%